THE CONCEPTION OF LᾹ MA'BŪDA IN TASAWUF; A QURANIC INTERPRETATION - Prasetia, Senata Adi; Najiyah, Siti Firqo (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
This article aimed to explore the concept of lā ma'būda from the Sufistic interpretation perspective. Lā ma'būda was one of the basic Sufism maqamat that must be passed by the salik therefore they can wuṣūl ilallāh (reach to Allah). This maqāmāt was the keyword in tasawwuf and most of tarekat developed in Indonesia, such as the qadīriyah, syadhiliyah, naqshabandiyah, shattariyah and so on. Lā ma'būda in the tarekat was defined as the activity of self-purification (tazkiyah al-nafs) from all materialism forms, hence he is able to purify his monotheism only to Allah. In the Sufistic interpretation perspective, lā ma'būda was interpreted as ‘nothing is worshiped except Allah’. This interpretation was similar with the terms of Syarī'a in the worshipping process and takhallī in the Sufi maqāmāt. Lā ma'būda or syarī'a or takhallī was the initial stage for the salik to wuṣūl ilallāh. This maqāmāt required an effort to purify oneself from all forms of bad behavior (takhallī) and adorn oneself with all praiseworthy qualities (taḥallī)